Geochronology and sedimentary environment at the Udu-dong archeological site, Chuncheon, South Korea. (September 2018) - Shin, Seungwon; Park, Yong-Hee; Choi, Jeong-Heon; Lim, Hyoun Soo; Shin, Sook-Chung; Cheong, Daekyo
The Udu-dong archeological site in Chuncheon, South Korea, dates back to the Proto–Three Kingdoms Period (approximately 100 BC to AD 350). Many artifacts, including some earthenware, have been excavated in these ancient dwelling sites. We applied three geochronological dating methods (radiocarbon, optically stimulated luminescence (OSL), and archeomagnetic dating) to the archeological remains of this large-scale human settlement and reconstructed the history of depositional processes prior to human settlement. The timing of the ancient community's settlement was investigated by radiocarbon dating of the charcoal fragments collected from old furnaces. Archeomagnetic dating allowed us to constrain the time period of the settlement's abandonment by dating the last use of fire. The timing and development of fluvial deposits underlying the settlement site were reconstructed by OSL dating combined with sedimentary facies analysis. Our results show that, following the deposition of coarse sediments starting 10, 000 years ago, the region formed a stable floodplain environment starting around 3000 years ago; people began to form clustered settlements approximately 50 years later. For the subsequent 150 years or so, the area was heavily used as a settlement site, with people evenly distributed across it, before eventual abandonment of the site around AD 200–250. Because the sedimentary deposits do not show any significant facies change during this period, we conclude that any catastrophic events were not the main reason for settlement abandonment. This study suggests that combining scientific and archeological analyses have significant benefits for studies of such archeological sites. Therefore, continuous collection of such data can provide important information for the excavation and protection of prehistoric or historic sites.